Examining impact of service user involvement: a follow-up study of user-led mental health service evaluation - Näslund, Hilda; Grim, Katarina; Markström, Urban (Frontiers in Psychiatry, 2025)
User-focused monitoring (UFM) is a method for service evaluation led by service users, aimed at enhancing quality and service user involvement. Our study examines the experienced outcomes following the completion of five UFM projects within Swedish mental health service programs. Specifically, we focus on the barriers and facilitators to integrating user-led evaluations into service program development. Through interviews with user monitors, managers, staff, and service users involved in these evaluation projects, we conducted a directed content analysis focused on preconditions, processes, and outcomes. Our findings indicate that UFM projects contribute to specific development measures and improved relationships within service programs but also to broader cultural change. However, a lack of trust among service users in actual change poses a significant obstacle to their involvement. Additionally, the absence of feedback regarding the implementation of change measures by service programs to service user groups risks reinforcing this lack of trust. To enhance the integration of evaluation results into quality development, early engagement with staff groups and clear implementation plans are recommended.